2021
DOI: 10.1186/s12951-021-01012-1
|View full text |Cite
|
Sign up to set email alerts
|

3D-printing magnesium–polycaprolactone loaded with melatonin inhibits the development of osteosarcoma by regulating cell-in-cell structures

Abstract: Melatonin has been proposed as a potent anticarcinogen presents a short half-life for osteosarcoma (OS). Cell-in-cell (CIC) structures play a role in the development of malignant tumors by changing the tumor cell energy metabolism. This study developed a melatonin-loaded 3D printed magnesium–polycaprolactone (Mg–PCL) scaffold and investigated its effect and molecular mechanism on CIC in OS. Mg–PCL scaffold was prepared by 3D-printing and its characteristic was determined. The effect and molecular mechanism of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…Compared with amputation surgery, limb salvage has become a preferred option for osteosarcoma with the advancement of surgical technology and the neoadjuvant chemotherapy regimen and is reported to have a better 5-year OS rate (4, 5). Limb salvage rates for osteosarcoma continue to increase owing to constantly improved curation including neoadjuvant chemotherapy, ablation techniques, bone transport techniques, radiotherapy regimens (6), and computer navigation techniques (7)(8)(9)(10). There are many factors that may influence the choice of surgical methods between limb salvage and amputation (11): apart from the tumor mass volume (TMV) and tumor stage, the multidisciplinary approach involving imaging, meticulous surgical procedures may have a great influence on the surgery choice for pediatric osteosarcoma (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with amputation surgery, limb salvage has become a preferred option for osteosarcoma with the advancement of surgical technology and the neoadjuvant chemotherapy regimen and is reported to have a better 5-year OS rate (4, 5). Limb salvage rates for osteosarcoma continue to increase owing to constantly improved curation including neoadjuvant chemotherapy, ablation techniques, bone transport techniques, radiotherapy regimens (6), and computer navigation techniques (7)(8)(9)(10). There are many factors that may influence the choice of surgical methods between limb salvage and amputation (11): apart from the tumor mass volume (TMV) and tumor stage, the multidisciplinary approach involving imaging, meticulous surgical procedures may have a great influence on the surgery choice for pediatric osteosarcoma (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…To further elucidate whether the mechanism of the neuroprotective effect of NOB is through inhibition of the Rho/ROCK signaling pathway, we established an OGD model of PC12 cells in vitro , examining the apoptosis, migration, cell viability and expression levels of related proteins after treatment of OGD PC12 cells with NOB, PA (an Rho/ROCK pathway agonist) ( 24 , 25 ) or NOB + PA. As shown in Figure 4 , the results revealed that the rate of apoptosis of PC12 cells in the NOB-treated group was less than that in the OGD model group. When treated with PA, apoptosis of OGD PC12 cells was accelerated, whereas treatment with NOB reduced PA-induced apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…It is necessary to be more cautious in the choice of implant loading drugs, and further experiments are needed. In addition, scholars have paid more and more attention to melatonin in the treatment of bone tumors in recent years, but the use of melatonin in the local drug delivery of titanium implants is rare [ 115 ].…”
Section: Discussionmentioning
confidence: 99%